KAJIAN EVALUASI KEBERHASILAN RUANG TERBUKA PUBLIK PADA KOMPLEKS STADION GELORA BUNG KARNO - Rigel Sandi Bahri; MM. Hizbullah Sesunan (Undagi : Jurnal Ilmiah Jurusan Arsitektur Universitas Warmadewa, 2024)
This research focuses on evaluating the public open spaces in the Gelora Bung Karno Stadium Complex. This research uses qualitative research methods through analysis and direct implementation in the field. The author used public open space reviews from experts and a questionnaire covering 102 respondents with online formulary filling techniques to evaluate this complex. Open spaces that have undergone an evaluation process can have a positive impact on the government and surrounding communities. At this time, people need open spaces that are responsive to needs and have elements of safety and comfort. The results of research conducted after conducting a survey and recapitulating the results of respondents, there are positive indications from the analysis of public open spaces and the public agrees that the public open spaces at the Gelora Bung Karno Stadium Complex have become successful open spaces.